Factors influencing short‐ and long‐term mortality after lower limb amputation1. (March 2014) - Scott, S. W. M.; Bowrey, S.; Clarke, D.; Choke, E.; Bown, M. J.; Thompson, J. P.
Summary Mortality after lower limb amputation is high, with UK 30‐day mortality rates of 9–17%. We performed a retrospective analysis of factors affecting early and late outcome after lower limb amputation for peripheral vascular disease or diabetic complications at a UK tertiary referral vascular centre between 2003 and 2010. Three hundred and thirty‐nine patients (233 male), of median (IQR [range]) age 73 (62–79 [26–92]) years underwent amputation. Thirty‐day mortality was 12.4%. On regression modelling, the risk of 30‐day mortality was increased in patients of ASA grade ≥ 4 (OR 4.23, 95% CI 2.07–8.63), p < 0.001 and age between 74 and 79 years (OR 3.8, 95% CI 1.10–13.13), p = 0.04 and older than 79 years (OR 4.08, 95% CI 1.25–13.25), p = 0.02. Peri‐operative (30‐day) mortality for these groups was 23.2%, 13.7% and 18.8%, respectively. Survival and Cox regression analysis demonstrated that long‐term mortality was associated with: age 74–79 years (HR 2.15, 95% CI 1.38–3.35), p = 0.001; age > 79 years (HR 2.78, 95% CI 1.82–4.25), p < 0.001; ASA grade ≥ 4 (HR 2.04, 95% CI 1.51–2.75), p < 0.001; out‐of‐hours operating (HR 1.51, 95% CI 1.08–2.10), p = 0.02; and chronic kidney disease stage 4–5 (1.57, 95% CI 1.07–2.30), p = 0.02. Anaesthetic technique was associated with long‐term mortality on survival analysis (p = 0.04), but not when analysed using regression modelling. Mortality after lower limb amputation relates to patient age, ASA, out‐of‐hours surgery and renal dysfunction. These data support lower limb amputations' being performed during daytime hours and after modification replace with 'of ' correctable risk factors.